If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + -3 = 15x + 7x Combine like terms: 3 + -3 = 0 0 = 15x + 7x Combine like terms: 15x + 7x = 22x 0 = 22x Solving 0 = 22x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-22x' to each side of the equation. 0 + -22x = 22x + -22x Remove the zero: -22x = 22x + -22x Combine like terms: 22x + -22x = 0 -22x = 0 Divide each side by '-22'. x = 0 Simplifying x = 0
| 50/x=161.25/15 | | -V=12V | | 3(1-8x)=32+5x | | 3+11x+10x^2=0 | | x^3+3x^4+4=0 | | a(y-4)+s(y-4)=0 | | a(y-4)+s(y-4)= | | 6y+2=12 | | 13(2+4)= | | X²-(X-2)²=5/2 | | log(2)8= | | 100s-77+83-34=36 | | Xsquared+7x-20=0 | | -5+k=30 | | log(100)10= | | -2x-1y=-12 | | 3u^2+5u-28=0 | | v4/5=84/5 | | 15x+2y=16.833 | | (-3x^4)(x^5+4x^2-3x^4)= | | 6p+8(p+7)=32+2p | | 8q-5=6 | | 13+3+3= | | XYZ+YZ+XZ=Z | | 8(2x-12)=24 | | 3(2b-5)=7b-12 | | (5x^2)(-2x^5)= | | (5K-3)+(K+2)+(3K-11)=[(5K-3)+1]+[(K+2)+2]+[(3K-11)+3] | | XYZ+XZ+YZ= | | 5(x-4)=12 | | 2x+4y+2z=6 | | 83x-2+23x-2=120 |